Caracterização e pedogênese de cambissolos de origem calcária no semiárido nordestino - Maniçoba, Francisco Elisângela (Universidade Federal Rural do Semi-Árido, 2018)
The Cambissolos (Inceptisol) stand out in the northeastern Semiárido, being the class of soil more found in areas in the Oeste Potiguar within the microregion on the Apodi Plateau. They are soils of good natural fertility and vary in terms of morphological, physical, chemical and mineralogical characteristics depending on the nature of the source material and the environments where they are formed. The objective of this study was to understand the pedogenesis of Cambissolos (Inceptisol) formed in limestone environment, inserted on the Apodi Plateau and as well as to understand how the formation of ferromanganous concretions occurs along the profiles and the influence of the material of origin in this phenomenon. The profiles studied that are inserted in the rural zone of the municipality of Upanema, within the Apodi Plateau. The physical analyzes were granulometry, clay dispersed in water and soil density and chemical analyzes were pH in water and KCl, electrical conductivity, available phosphorus, exchangeable bases, exchangeable aluminum, extractable acidity, calcium carbonate (CaCO3) and total organic carbon (COT); being estimated the indexes of silt/clay ratio, flocculation degree and made the textural classification for physical analysis and ΔpH, cation exchange capacity at pH 7.0 (T), base saturation (V), exchangeable aluminum saturation (m) and exchangeable sodium percentage (PST) for the chemical analyzes. The soil profiles presented a clay texture, with the exception of P4 which has a more sandy texture. The ADA levels were elevated and increasing with depth except for P4. The degree of flocculation in the Cambissolos (Inceptisol) profiles were low in the surface horizons and tended to increase in depth. The chemical analyzes showed pH values close to 7,0 and values of electrical conductivity (CE) were low in all profiles. The available phosphorus content very low. The exchangeable base contents were low in all soil profiles. The analysis of CaCO3 equivalent showed that all the profiles studied presented low levels of CaCO3, even if they were of calcareous origin. The COT decreased in depth and presented a variation in these values in subsurface horizons of P2 and P4. The soils presented low values of (T) and still high values of (V) with the exception of P4 that was classified as dystrophic. The ferromanganous concretions are present in all the horizons of all the studied profiles and present in the concentric form and of variable size. In the SiBCS classification, the soils are classified as Cambissolo Háplico Tb Eutrófico típico (P1), Cambissolo Háplico Tb Eutrófico típico (P2), Cambissolo Háplico Tb Eutrófico típico (P3), and Cambissolo Háplico Tb Distrófico latossólico (P4). The soils are soils with variable texture always presenting increasing clay content in depth. They have alkaline and electronegative character low carbonate content and high base saturation, except for the "latossolic" Cambissolo (Inceptisol). The ferromanganous concretions are present in all horizons of the evaluated profiles with average size of 3 mm
Monografia
Keywords: Rochas sedimentares; Chapada do Apodi; Concreções ferromanganosas; Sedimentary rocks; Apodi Plateau; Ferromanganous concretions; CIENCIAS AGRARIAS::AGRONOMIA